Scoping exercise to develop a storybook to support children's education during the COVID-19 pandemic - Alicia Demirjian; Rowshonara Syeda; Magdalena Hann; Rosalie Allison (BMJ Publishing Group, 2021)
Objective In June 2020, as COVID-19 lockdown measures were eased in the UK, this scoping exercise aimed to rapidly identify topics to cover within a children's online storybook 'My Back to School Bubble', designed to support the return to school.Methods An email invitation was sent to 71 known contacts within networks across Public Health England, local authorities, health protection teams and contacts within the Department for Education. Following online publication of 'My Back to School Bubble', users were asked to provide informal feedback via an online survey to ask about their impressions of the story.Results Findings from the 31 responses highlighted that children are likely to hold differing feelings regarding COVID-19, depending on their own temperament and lockdown experiences, including changes in relationships with family and friends. Following the launch of 'My Back to School Bubble' e-storybook, 21 users provided feedback via survey. Fourteen respondents (67%) indicated that the storybook was a useful tool for providing support to children, and twelve (57%) reported that the resource helped children understand their own feelings.Recommendations Clear, accurate information about the new school environment should be provided in the context of COVID-19. It is especially important to support children with special educational needs and disabilities, including those with autism. Encouraging children to take ownership of their health and hygiene behaviours, such as handwashing, will help to normalise this and prevent the spread of infection. Lessons learnt from the development of 'My Back to School Bubble' online storybook suggest the clarity of imagery could be improved to better support children with autism. Future work should focus on longitudinal and qualitative research. This should include the long-term effects of the pandemic on children's development and education, effects on mental health and resilience, peer socialisation, and ability to cope with life-changing events.